Effect of filler dispersion and dispersion method on the piezoelectric and magnetoelectric response of CoFe2O4/P(VDF-TrFE) nanocomposites - Martins, P. (2014)
Nanoparticle dispersion is assumed to be one of the key factors in composites performance and, in particular, for improving magnetoelectric (ME) coupling in polymer composites. To ensure a good dispersion, one of the most popular strategies is the use of surfactants, nevertheless in the case of magnetic nanoparticles–polymer composites, aspects such as the chemical and processing complexity, thermal stability, costs and health issues of such additives have severely constrained the development of upscaled applications of such composites. In this way, the dispersion of cobalt ferrite (CoFe2O4) nanoparticles in poly(vinylidene fluoride)-trifluorethylene, P(VDF-TrFE), matrix and its role in the piezoelectric, magnetic and magnetoelectric properties of the nanocomposite has been studied by preparing samples via two alternative dispersion routes: ultrasound and citric acid nanoparticle surfactation. No substantial differences have been detected in the ferroelectric, piezoelectric, magnetic and magnetoelectric response of samples prepared with and without surfactants, leading to a simplified large-scale production.